Comparative Studies in Society and History (Cambridge)
Comparative Studies in Society and History (CSSH) is an international forum for new research and interpretation concerning problems of recurrent patterning and change in human societies through time and in the contemporary world. CSSH sets up a working alliance among specialists in all branches of the social sciences and humanities as a way of bringing together multidisciplinary research, cultural studies, and theory, especially in anthropology, history, political science, and sociology
Keywords: Sociology